The global prevalence of autism spectrum disorder: A three-level meta-analysis - Talantseva, Oksana I.; Romanova, Raisa S.; Shurdova, Ekaterina M.; Dolgorukova, Tatiana A.; Sologub, Polina S.; Titova, Olga S.; Kleeva, Daria F.; Grigorenko, Elena L. (Frontiers in Psychiatry, 2023)
Autism spectrum disorder (ASD) is one the most disabling developmental disorders, imposing an extremely high economic burden. Obtaining as accurate prevalence estimates as possible is crucial to guide governments in planning policies for identification and intervention for individuals with ASD and their relatives. The precision of prevalence estimates can be heightened by summative analyses of the data collected around the world. To that end, we conducted a three-level mixed-effects meta-analysis. A systematic search of the Web of Science, PubMed, EMBASE, and PsycINFO databases since 2000 up to 13 July 2020 was performed, and reference lists of previous reviews and existing databases of prevalence studies were screened. Overall, 79 studies were included in the analysis of ASD and 59 - in the analysis of previously existing relevant diagnoses: 30 for Autistic Disorder (AD), 15 for Asperger Syndrome (AS), and 14 for Atypical Autism (AA) and Pervasive Developmental Disorder - Not Otherwise Specified (PDD-NOS); these research reports covered the period from 1994 to 2019. Pooled prevalence estimates were 0.72% (95% CI = 0.61-0.85) for ASD, 0.25% (95% CI = 0.18-0.33) for AD, 0.13% (95% CI = 0.07-0.20) for AS, and 0.18% (95% CI = 0.10-0.28) for combined group of AA and PDD-NOS. Estimates were higher (1) for the studies that used records-review surveillance rather than other designs; (2) in North America compared with other geographical regions; and (3) in high-income compared with lower-income countries. The highest prevalence estimates were registered in the USA. There was an increase in autism prevalence estimates over time. The prevalence was also significantly higher for children aged between 6 to 12 years compared to children under the age of 5 and over the age of 13 years.